An all-in-one biomimetic iron-small interfering RNA nanoplatform induces ferroptosis for cancer therapy. (August 2022) - Huang, Siming; Le, Hongbo; Hong, Guobin; Chen, Guosheng; Zhang, Fang; Lu, Liejing; Zhang, Xiang; Qiu, Ya; Wang, Zhe; Zhang, Qinyuan; Ouyang, Gangfeng; Shen, Jun
Abstract: Iron-dependent ferroptosis is a promising therapeutic strategy for cancers. However, the sustained overexpression of the antioxidant glutathione (GSH) in cancer cells substantially limits its therapeutic effect. Seeking efficient approaches that can perform high GSH depletion efficiency remains a significant task. Herein, we construct an all-in-one nanoplatform with functions of tumor targeting, monitoring and treatment for cancer ferroptosis therapy by constructing a homotypic cancer cell membrane-camouflaged iron-small interfering RNA nanohybrid (CM-Fe-siR). The SLC7A11-targeted siRNA in the nanohybrid inhibits the biosynthesis of GSH by cutting off the supply of intracellular cystine, an essential ingredient in GSH synthesis, which subsequently results in the accumulation of reactive oxygen species (ROS) that are generated from Fenton reaction induced by iron. Meanwhile, the intracellular deficiency of GSH inactivates glutathione peroxidase 4 (GPX4, a lipid repair enzyme), which further increases the accretion of lipid peroxides to enhance iron-induced ferroptosis. This biomimetic nanohybrid shows a remarkable anti-cancer effect by triggering sustainable and efficient ferroptosis via these multiple synergistic actions. Besides, the nanohybrids enable in vivo magnetic resonance imaging (MRI) monitoring of therapy. The biomimetic CM-Fe-siR all-in-one nanoplatform may provide an efficient means of ferroptosis therapy for cancers. Statement of Significance: Ferroptosis therapy based on the Fenton reaction of iron nanomaterials has aroused much attention in cancer treatment; however, the therapeutic efficacy is greatly inhibited by the sustained overexpression of the antioxidant GSH in cancer cells. It is of great importance to exploit more reagents or techniques performing high GSH depletion efficiency. Here, we facilely construct an all-in-one cancer cell membrane-camouflaged iron-siRNA nanoplatform, which possesses good biosafety, tumor-targeting, and noninvasive MRI monitoring capabilities. It effectively inhibits the GSH synthesis, and further simultaneously promotes the ROS accumulation and GPX4 inactivation, leading to enhanced cancer ferroptosis. This work highlights that the biomimetic iron-siRNA nanohybrids have a high potential in clinical application for imaging-guided cancer ferroptosis therapy. Graphical abstract: Image, graphical abstract